2008
DOI: 10.3354/dao01965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three molecular methods for the detection of Pilchard herpesvirus in archived paraffin-embedded tissue and frozen tissue

Abstract: Two epizootics affecting pilchards Sardinops sagax neopilchardus have been observed over their entire geographical range off the Australian coastline. The first occurred in 1995, involving high mortality (at least 10%) that devastated the pilchard population. The second occurred in 1998 and involved even higher mortality (70%). Both epizootics moved rapidly against the prevailing Leeuwin and East Australian currents from a defined point of origin. A herpesvirus, pilchard herpesvirus (PHV), was determined to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The topology was also identical with that of the Bayesian or distance matrix trees (not shown). Although from most alloherpesviruses, another part of the terminase gene has been amplified by PCR, choosing this region allowed us to include the HV described from the Australasian pilchard [25] into a phylogenetic analysis for the very first time. From the putative PHV, this is the only nt sequence available [12] .…”
Section: Phylogenetic Calculationsmentioning
confidence: 99%
“…The topology was also identical with that of the Bayesian or distance matrix trees (not shown). Although from most alloherpesviruses, another part of the terminase gene has been amplified by PCR, choosing this region allowed us to include the HV described from the Australasian pilchard [25] into a phylogenetic analysis for the very first time. From the putative PHV, this is the only nt sequence available [12] .…”
Section: Phylogenetic Calculationsmentioning
confidence: 99%
“…Involvement of an infectious agent was suggested, and PCR analysis revealed the putative involvement of a herpesvirus (Tham & Moon, 1996), which was soon confirmed by EM . Diagnostic tools for detection of the pilchard herpesvirus have been developed (Crockford et al, 2005;Crockford et al, 2008), revealing that the virus is now endemic in Australian pilchard populations . Although the pilchard herpesvirus has not yet been isolated in cell culture, hampering further studies, limited phylogenetic analysis showed its relation to other fish and frog herpesviruses (Doszpoly et al, 2011a).…”
Section: Pilchard Herpesvirusmentioning
confidence: 99%
“…Real-time PCR analysis was conducted using a Bio-Rad CFX96TM real-time PCR detection system on a C1000TM thermal cycler. Real-time PCR primers and cycling conditions were as described by Crockford et al (2008). Data collection and real-time analysis occurred at the annealing step of each cycle and melt-curve data collection and analysis occurred at each increment in the latter 40 cycles.…”
Section: Determination Of Phv Presence In South African Sardinementioning
confidence: 99%
“…Samples that failed to record a Cq value or failed to produce a specific melt peak were considered to be negative. For each PCR, a standard curve was constructed by spiking known quantities of plasmid DNA, purified from a PHV clone obtained from the Department of Fisheries in Western Australia (see Crockford et al 2008), into the homogenised gill tissues prepared from a PHV-negative sardine. DNA added for sensitivity testing was spiked into tissues in order to achieve final concentrations that ranged from 13 ng μl-1 to 1.3 × 10-11 ng μl-1 in the reaction tubes.…”
Section: Determination Of Phv Presence In South African Sardinementioning
confidence: 99%
See 1 more Smart Citation